AS PRÁTICAS DE MODELAGEM MATEMÁTICA NA EDUCAÇÃO BÁSICA DO ESTADO DO PARANÁ - Penteado, Daniele Regina (2015)
This research was carried out from the subject Mathematical Modeling, with the main objective of making available to view aspects considered relevant on mathematical modeling practices within the State of Parana Basic Education. The study objective was to analyze the practices in Mathematical Modeling constant at 65 Experiences Reports presented in meetings Paranaenses Modeling and Mathematics Education (EPMEM) conducted between 2004 and 2012, totaling five editions. Before the events shown in these reports, the main question about the Mathematical Modeling it long answer can be expressed in the following question: What is evident practices Mathematical Modelling developed in the State of Parana Basic Education, from the reports presented in EPMEM ? Of the 65 reports presented in five editions of the EPMEM and contained in the Annals of events, 28 reports dealing with the Paraná State Basic Education came to constitute the corpus of research and thus were analyzed in detail. Methodological aspects undertaken in this research are qualitative, with meta-analytic design and processing of data according to content analysis from the perspective of Bardin (2011). Reading and coding of all materials were made with the assistance of the software Atlas / Ti. The methodological and theoretical frameworks used basically include Bardin (2011), Franco (2005), Alves- Mazzotti & Gewandsznajder (2004), Larocca (2005 ), Bicudo (2014), D'Ambrosio (2004), Fiorentini (1995), Kluber (2007, 2010), Burak (1992) and Paraná (2008),among others. The results of this research point to some reflections and considerations regarding analyzed practices, which have shown that mathematical modeling is being inserted in the school context in different ways, because of the diversity of modeling concepts, but, in general, impressions of teachers and students are very favorable. After the categorization and analysis performed, we arrive at an overview of how these practices are taking place in classrooms and what the motivations that lead teachers to develop them believe that these elements that can serve as a starting point for further research to be conducted in the area of Mathematical Modeling.